Observations of amphibian, reptile and some mammal species in the area of Šaleška jezera near Velenje during the 2015–2017 period - Anja Bolčina; Jan Gojznikar; Rudi Kraševec; Matic Gabor; Blaž Vrhovšek (Natura Sloveniae)
In this contribution we present our observations of amphibians, reptiles and some mammals from the area of Šaleška jezera (lakes) near Velenje in northern Slovenia. This area refers to three lakes – Velenjsko jezero, Šoštanjsko jezero and Škalsko jezero, which were formed in the 20th century as a consequence of underground lignite mining. The landscape is still changing due to an ongoing subsidence of the valley caused by continuous mining, which constantly affects the surface water bodies and habitats. The changes are so apparent that they could be measured in weeks if not days. New records on the occurrence of 9 amphibian, 7 reptilian and 9 mammalian species were made in the region during our field work carried out from 2015 to 2017. Three of these species are listed on Annex II of the EU Habitats Directive – Emys orbicularis, Bombina variegata and Triturus carnifex, and additional eight on Annex IV of this directive – Bombina variegata, Hyla arborea, Rana dalmatina, Triturus carnifex, Emys orbicularis, Lacerta viridis, Podarcis muralis and Natrix tessellata. We also recorded two introduced species – Dama dama and Trachemys scripta.